Estimating the Selectivity of Gill Net Fishing Equipment and Bioecology in an Effort to Preserve the Conservation of Lencam Fish Populations in Maitara Island Waters - Muksid, Jurdi; Baharuddin, Abd. Haris; Ajan, Yusrifal; Tangke, Umar (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aims to estimate the selectivity of gill net fishing gear operated by fishermen on Maitara Island, analyze population conditions, sustainable potential and appropriate size for catching lencam fish as well as the appropriate mesh size in the exploitation of lencam fish in the waters of Maitara Island so that its management can be sustainable. The use of experimental fishing methods with data analysis in the form of selectivity of fishing gear, population parameters, determination of suitable catch sizes and determination of mesh size. The results of the study showed that the fishing gear operating in Maitaran Island waters has a mesh size of 2.5 inches where the gill net fishing gear is classified as non-selective because it generally catches lencam fish that have not yet spawned, which is smaller than 41.4 cmFL and the small size of the mesh size affects the parameters. lencam fish population in the waters of Maitara Island with fishing mortality higher than natural mortality and the level of exploitation has entered the over fishing category.